Law Schools at Founding and Today - Russell K. Osgood; Jacob Glickfield (Washington University Journal of Law & Policy, 2017)
This Essay offers a historical perspective detailing the development of Missouri’s Constitution and the history of common law legal education by focusing on the founding of the Washington University Law Department. The authors address some suggestions by other scholars on how to modernize education including conversion to a two-year curriculum. While reflecting on the past, the authors suggest that a longer, but non-rigid, curriculum may be the only feasible way to structure legal education and offers several alternative structures for modern legal education. They discuss the pros and cons of their proposal, highlighting the need for social discussion concerning legal education and urge people considering the topic not to get too bogged down in details.
Keywords: Washington University; law department; Washington University School of Law; legal education; Missouri Constitution; modern legal education; ABA accreditation